The role of management games as a learning tool - Roy, Subhadip; Adhikari, Atanu (2006)
Management games are gaining more and more importance in today's workplaces. They not only provide a respite from daily work but also help to imbibe within the players a complex concept without the use of the lecture method of teaching and with the help of fun element added in the game. They have now crossed the boundaries of organizations (where they used to be played primarily) and are now used in educational institutes like Business Schools to make the students acquainted with concepts that are difficult to explain, unless experienced. This article speaks about the origin of management games, the use of management games and the steps in conducting a game along with its advantages and disadvantages. - Reproduced.
Keywords: Management